Neuroprotective effect of selumetinib on acrolein-induced neurotoxicity - Hui-Ju Huang; Hsiang-Tsui Wang; Ting-Yu Yeh; Bo-Wei Lin; Young-Ji Shiao; Yu-Li Lo; Anya Maan-Yuh Lin (Scientific Reports, 2021)
Abstract Abnormal accumulation of acrolein, an α, β unsaturated aldehyde has been reported as one pathological cause of the CNS neurodegenerative diseases. In the present study, the neuroprotective effect of selumetinib (a MEK–ERK inhibitor) on acrolein-induced neurotoxicity was investigated in vitro using primary cultured cortical neurons. Incubation of acrolein consistently increased phosphorylated ERK levels. Co-treatment of selumetinib blocked acrolein-induced ERK phosphorylation. Furthermore, selumetinib reduced acrolein-induced increases in heme oxygenase-1 (a redox-regulated chaperone protein) and its transcriptional factor, Nrf-2 as well as FDP-lysine (acrolein-lysine adducts) and α-synuclein aggregation (a pathological biomarker of neurodegeneration). Morphologically, selumetinib attenuated acrolein-induced damage in neurite outgrowth, including neuritic beading and neurite discontinuation. Moreover, selumetinib prevented acrolein-induced programmed cell death via decreasing active caspase 3 (a hallmark of apoptosis) as well as RIP (receptor-interacting protein) 1 and RIP3 (biomarkers for necroptosis). In conclusion, our study showed that selumetinib inhibited acrolein-activated Nrf-2-HO-1 pathway, acrolein-induced protein conjugation and aggregation as well as damage in neurite outgrowth and cell death, suggesting that selumetinib, a MEK–ERK inhibitor, may be a potential neuroprotective agent against acrolein-induced neurotoxicity in the CNS neurodegenerative diseases.